PENGARUH CSR DAN GCG TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATING - Melani, Sulistia; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to provide empirical evidences of the influence of social responsibility disclosure, good corporate governance to the firm value which is moderated by profitability. The population is manufacturing companies which are listed in Indonesia Stock Exchange during 4 year periods i.e. 2012-2015. The sample collection has been carried out by using purposive sampling method, the number of samples which have been obtained are 224 observation data. The data analysis technique has been done by using Moderated Regression Analysis (MRA). Based on the result of the analysis and hypothesis test, it can be concluded that: (1) Corporate Social Responsibility disclosure gives significant and positive influence to the firm value; (2) the implementation of Good Corporate Governance give signfcant and positive influence to the firm value. When the company implements the GCG system, it will enhance the corporate performance which give influence to the enhancement of the share price of the company; (3) size control variable does not give any influence to the firm value. Large firm size cannot guarantee its firm value will be high; (4) leverage control variable does not give any influence to the firm value; (5) Corporate Social Responsibility disclosure can moderate the influence of the ROA on firm value. The high ROA value will attract the attention of the investors to invest their capital and it gives influence to the enhancement of stocks performance in stock exchange; (6) the implementation of Good Corporate Governance can moderate the influence of the ROA on firm value; (7) the ROA can mediate the influence of leverage to the firm value whereas the ROA cannot mediate the influence of size to the firm value.Keywords: GCG, CSR, Size, leverage, Profitability.